Unearthing Temasek : earthenware and site function in 14th-century Singapore - Ang, Caroline Leng Lee (2019)
The study of ceramics in Southeast Asia has often focused on stoneware and porcelain, with less focus on earthenware ceramics. However, as earthenware ceramics are found in large numbers in many Southeast Asian sites, studies of earthenware can reveal important information that slips through the gaps in textual sources. Presently, studies of earthenware in Singapore tend to focus on decorative techniques and motifs. This thesis thus contributes to the literature by looking beyond style to analyse the form and material of the earthenware. This thesis undertakes a quantitative analysis of rim sherds excavated from St. Andrews Cathedral (STA) and Fort Canning Spice Garden (FTCSG). Functional analysis of the rim sherds is carried out to determine common vessel functions used in 14th-century Singapore. Thereafter, proportional comparison of the earthenware types at each site is conducted to suggest the site functions of STA and FTCSG.